Role of Remote Sensing Data and Geographic Information Systems to Support in Landuse Planning Activity at Urban Area - Santoso, Sugiharto Budi (Forum Geografi, 1998)
Land order in an urban area that is not based on complete and reasonable spatial information an cause an unintegrated development program. Therefore, spatial information that can analyze the information to make a decision of land order is greatly needed. To present the most reasonable physical data of the urban can use the data of remote sensing as a main source, because the data an present not only a high temporal resolution, but also a complete object. Along with the advance of computer-based GIS, the data of remote sensing can be integrated with GIS. In addition, the data sharing can be used in various sectors. Thus, both updating and mutual exchanging of data can be done easly.